The Role of Life Events/Contextual Factors and Cannabis Use in Patterns of Other Drug Use Among Young Adult Cannabis Users in Los Angeles: A Qualitative Inquiry. (April 2020) - Fedorova, Ekaterina V.; Roth, Alexis M.; Cepeda, Alice; Wong, Carolyn F.; Iverson, Ellen; Lankenau, Stephen E.
This analysis examined the role of impactful life events/stressful contextual factors and cannabis use in the patterns of illicit drug use. It utilized semi-structured qualitative interviews with 40 young adult medical cannabis patients and 22 non-patient users collected in Los Angeles during 2014–2015. Three patterns of illicit drug use emerged based on participants' narratives: regular/problematic, recreational/occasional, and never users. Among regular/problematic users, a common theme was the lasting impact of traumatic life events or stressful contextual factors on transition to and away from problematic drug use, and using cannabis to cope with negative after effects of drug use. In contrast, most recreational/occasional and never users, who reported impactful life events or stressful contextual factors, used cannabis to cope with those experiences. Family history of addiction and acceptance of cannabis use within a family as protective factors against illicit drug use among some recreational/occasional and never users was an unexpected finding.